Infection risks associated with care in prehospital care: impacts on patient safety (Research, Society and Development, 2020)
Objectives: To identify incidents related to the risk of infection in land mobile pre-hospital care and to analyze the interfaces of this care with patient safety. Method: Observational, prospective study with evaluation of 239 occurrences. Data were analyzed using Epi-info and Statistical Package for Social Science statistical programs. The research was submitted to and approved by the ethics committee under registration number: 2,764,855. Results: 218 (92.8%) occurrences there was no hand hygiene between the procedures; gloves were not exchanged in 159 (69.1%) cases; hand hygiene was not performed before applying the dressing in 19 (46.3%) cases involving injuries; peripheral venipuncture was not performed using aseptic technique in 101 (60.8%) cases and in 06 occurrences aseptic bladder catheterization was not performed (85.7%). Conclusion: It is observed that mobile prehospital care is an environment of risk for infection associated with the care process. The results achieved in the research demonstrate that the objectives were achieved by presenting, quantitatively, the specific points that put the patient at risk with regard to their safety. Thus, it is necessary to invest in facilitating strategies for the proper performance of hand hygiene and control of the risk of infection in ambulance services, as well as the implementation of Patient Safety Centers strategically and operationally adapted to the mobile prehospital follow-up.